2004
DOI: 10.1191/0267658304sr238oa
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effects of first language influence on second language pragmatic processes from a syntactic deficit perspective

Abstract: Explaining the persistent optional use of overt forms of certain grammatical properties in adult second language acquisition (SLA) raises the question of whether or not such difficulties are directly attributable to first language (L1) influence. Using Sperber and Wilson’s Relevance Theoretic framework (1986/95), this paper considers how a grammatical deficit could contribute to non-native-like pragmatic processing at the level of explicature formation=recovery, on the assumption that the decoding of grammatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
1
4
0
1
Order By: Relevance
“…Similar results have been reported in studies of ESL learners with different first languages (Bardovi-Harlig, 1998;Bardovi-Harlig & Bergstrom, 1996;Collins, 2005;Coppieters, 1987;Guiora, 1983;Hinkel, 1992Hinkel, , 1997Liszka, 2004). It is particularly important to note that the same pattern even applies to learners who have acquired near-native like proficiency (Coppieters, 1987).…”
Section: Introductionsupporting
confidence: 84%
“…Similar results have been reported in studies of ESL learners with different first languages (Bardovi-Harlig, 1998;Bardovi-Harlig & Bergstrom, 1996;Collins, 2005;Coppieters, 1987;Guiora, 1983;Hinkel, 1992Hinkel, , 1997Liszka, 2004). It is particularly important to note that the same pattern even applies to learners who have acquired near-native like proficiency (Coppieters, 1987).…”
Section: Introductionsupporting
confidence: 84%
“…Turning to the present perfect, Liszka (2004Liszka ( , 2005 tested L1 Chinese, German and Japanese speakers of advanced L2 English on the acquisition of the (British) English present perfect, using a form-interpretation task. The results showed that the German learners produced the present perfect 58% of the time in present perfect contexts, similar to 56% for the Japanese and 47% for the Chinese.…”
Section: Acquisition Of Tense/aspect In the L2mentioning
confidence: 99%
“…Menurut (Sarah A. Liszka, 2004) dalam penelitian "Exploring the effects of first language influence on second language pragmatic processes from a syntactic deficit perspective" berusaha mempertimbangkan fungsi gramatikal yang dapat berkontribusi pada pemrosesan pragmatis pada tingkat pembentukan explicature atau pemulihan, dengan asumsi bahwa penguraian pengetahuan tata bahasa secara logis memulai pengembangan pragmatis yang diperlukan untuk pembentukan. Penelitian tersebut menggunakan kerangka teori Relevansi Sperber dan Wilson.…”
Section: Pendahuluanunclassified